Graphene oxide-modified zinc anode for rechargeable aqueous batteries. (2nd February 2019) - Zhou, Zhubo; Zhang, Yamin; Chen, Peng; Wu, Yutong; Yang, Haochen; Ding, Haoran; Zhang, Yi; Wang, Zhongzhen; Du, Xu; Liu, Nian
Graphical abstract: Highlights: Graphene oxide was uniformly coated onto the zinc anode. Graphene oxide coating suppresses the dissolution problem of zinc anodes. Graphene oxide alleviates the passivation problem of zinc anodes. Graphene oxide-modified Zn metal anode shows enhanced rechargeability. Abstract: Li-based batteries are intrinsically unsafe because of their use of flammable organic electrolyte. Great efforts are being made to develop solid electrolytes or safer alternative battery chemistries, among which Zn-based batteries stand out for their high energy density and good compatibility with aqueous electrolyte. Theoretically, Zn-air batteries have very high volumetric energy density, which is ∼85% of that of Li-S batteries. However, Zn anodes have poor cycling performance because of their passivation (insulating discharge product ZnO) and dissolution (soluble zinc species in alkaline electrolytes) problems. In this work, we overcome these problems by modifying Zn anode with graphene oxide (Zn@GO) by a facile solution casting method. The GO layers on the Zn surface can deliver electrons across insulating ZnO, slow down the Zn intermediates from dissolving into the electrolyte, and thereby enhance the utilization and rechargeability of Zn anodes. As a result, the Zn@GO anode containing only 1.92 wt% GO showed improved cycling performance compared to that of the unmodified Zn mesh. The accumulated areal discharge capacity of the Zn@GO anode is 128% of that of the unmodified Zn mesh. The Zn@GO anode reported here can potentially be paired with oxygen cathode to form safe high-energy rechargeable batteries, and be used in large scale applications, ranging from electric vehicles, to grid-scale energy storage. The surface modification method reported here can also potentially be applied to other high-capacity electrodes that undergo passivation or dissolution issues.